Penerapan Sistem Suara Terbanyak pada Pemilu Legislatif Tahun 2009 sebagai Perwujudan Demokrasi - Situmorang, Julita; Situmorang, Tonny P. (Politeia: Jurnal Ilmu Politik, 2017)
In a democratic country, the thing that is considered the most important and always of concern is peoples participation in determining the direction of state policy. This is a necessity, given the position of the people as holders of sovereignty. General elections as one of the activities carried out by the government periodically based on the principles of democracy, is an implementation of peoples participation. As the holder of sovereignty in determining state policy, through the election of representatives of the people to sit in parliament and subsequently carried out by the executive or the government. As a democracy based on Pancasila, Indonesia has repeatedly held General Elections. When calculated, at least 10 (ten) times the General Election has been held which elects the peoples representatives and the President. In 2004, a separation between the selection of Legislative Members with the Presidential Election. The purpose of this paper is to determine the extent of the implementation of democracy, through the holding of the 2009 legislative elections, by implementing the most votes system to elect legislators. This writing is intended to analyze the 2009 legislative elections, in order to get a real picture that is used as reference material and practical knowledge by various parties.Â